The Effect Of Compensation And Work Motivation On Employee Job Satisfaction At PT.Agro Muara Rupit - Fini Elpionita; Sri Ekowati (Utami Publisher, 2025)
This study aimn to find out the influence of compensation and work motivation on employee job satisfaction at PT. Agro Muara Rupit,both partially and simultaneously. Several factors are discussed in this research,including compensation and work motivation. The object of this study consists of 40 employees of PT. Agro Muara Rupit. The data collection methods used in this study include observation and the distribution of questionnaires. The data analysis techniques applied in this research consist of instrument testing, classical assumption testing, respondent response analysis, multiple linear regression analysis,hypothesis testing,and the determination coefficient analysis(R2). The results of the study indicate that the compensation variable has a positive and significant effect on employee job satisfaction at PT. Agro Muara Rupit. The work motivation variable also has a positive and significant influence on employee job satisfaction at PT. Agro Muara Rupit. Therefore, based on the findings of this research, it can be concluded that compensation and work motivation have both partial and simultaneous effects on employee job satisfaction at PT. Agro Muara Rupit.